Lead Concentrations in Human, Cow's, and Goat's Milk in Rural Appalachia. - Wisniewski, Kana; Daniels, Natalie Kruse; Chertok, Ilana (Journal of Appalachian Studies)
Lead is neurotoxic particularly for the developing infant brain, and lead exposure should therefore be limited from environmental and nutritional sources. This study examined the lead concentrations of human, cow's, and goat's milk samples from Appalachia and compared them to the safety limits set by the World Health Organization. Twenty breastfeeding women residing in Appalachian Ohio provided human milk samples, while samples of cows' and goats' milk from local dairies were collected. The milks were analyzed for lead concentrations using inductively coupled plasma mass spectrometry (ICP-MS). Factors examined included maternal residential location, age of residence, water source, workplace exposure, smoking exposure, and sociodemographic characteristics. Overall, the milk samples' lead levels were within the safety limits set by the WHO, and human milk lead levels were comparable to locally sourced cow's and goat's milk. Significant factors associated with higher lead levels in human milk samples were older houses (p = 0.001) and the number of years living in the house (p = 0.013). Lead levels in human milk of mothers in the study were within the WHO safety limits, while factors associated with higher lead levels were identified.